Core Factors for Software Projects Success - Mohammad Ibraigheeth; Syed Abdullah Fadzli (Society of Visual Informatics, 2019)
The successful software project can be defined as the project that meets the planned quality, cost, schedule, and effort. It has been suggested that there are many reasons which might lead to software project success.Â Several success and failure factors for particular projects were discussed in the literature. This paper aims to identify the most common success factors through reviewing a set of software project reports and case studies. In order to fully understand reasons behind the project success, the reasons behind project failure and the definition of failure itself are discussed. Furthermore, case studies of successful and failed software projects are described. This paper also investigates techniques that have been developed to increase software project success rate and decrease probable failures.